IMPLEMENTASI REKAM MEDIS ELEKTRONIK DALAM ASPEK KEAMANAN DATA PASIEN DI TPMD dr. ELVI SILVIA - Octav, Berliana; Wahab, Syaikhul (Jurnal Infokes (Informasi Kesehatan), 2024)
Electronic medical records are computerized health information systems containing patient medical data. The use of electronic medical records has security, data protection including aspects of confidentiality, authentication, availability, and access control. The study aims to determine the implementation of electronic medical records in terms of patient data security at the Independent Practice of Dr. Elvi Silvia. The study uses a qualitative descriptive method that describes and interprets the situation. The research subjects are the number of workers at the Independent Practice of Dr. Elvi Silvia, the object used for electronic medical records. The data collection technique used is triangulation, which combines various data collection techniques. The research instruments are interview guidelines and observation guidelines. The analysis of data collection carried out includes data reduction, data presentation, and drawing conclusions from the research results. The results of the study indicate that patient data security in terms of confidentiality is appropriate, there is a username and password for each user, and an automatic logout feature. Patient data security in terms of authentication shows the validity of the data, indicated by an electronic signature. Patient data security according to the availability aspect shows suitability because this electronic medical record can be accessed anytime, anywhere via Google Chrome and Mozilla Firefox. Patient data security in terms of access control is appropriate, using usernames and passwords according to access rights, but not all features can be used by staff. Keywords: Electronic medical records, data security, service facilities